Kualitas Dadih dengan Pemberian Daun Singkong sebagai Pakan Suplemen - E Roza; M.S Suardi; E Nurdin; S.N Aritonang (Universitas Andalas, 2012)
The purpose of this study was to determine the effect of the use of cassava leaves as feed supplement on the quality of buffalo curd in cattle traditionally reared. This study used 20 female buffaloes at second and third lactation Sijunjung district. The method was used a completely randomized design ( CRD ) with 4 treatments and 5 replications. The material was used a feed supplement in the pellets form that consisted of urea (7.5 %) , saka (20 %), cassava leaf meal (10 %), bran (37.5 %), salt (8 %), cement (10 %), mineral mixture (2 %) and water (5 %). The treatment were supplementation of cassava leaves as much as A : 0 kg / head / day , B : 0.5 kg / head / day , C : 1.0 kg / head / day and D : 1.5 kg / head / day. Variables measured were moisture content, protein, and the acidity of the curd. The results showed that feeding supplements significant influence ( P < 0.01 ) on milk composition ( moisture 80.93 % , protein 7.95 %, viscosity 2.68 Cpa and acidity 1.22 %). It was concluded that the feeding supplements of 1.5 kg/head/day (Treatment D) may increase the protein, acidity , viscosity and decrease of whey .